Anisotropy in the lowermost mantle beneath the Indian Ocean Geoid Low from ScS splitting measurements. (15th February 2017) - Padma Rao, B.; Ravi Kumar, M.; Singh, Arun
Abstract: The Indian Ocean Geoid Low (IOGL) to the south of Indian subcontinent is the world's largest geoid anomaly. In this study, we investigate the seismic anisotropy of the lowermost mantle beneath the IOGL by analyzing splitting of high‐quality ScS phases corrected for source and receiver side upper mantle anisotropy. Results reveal significant anisotropy ( ∼ 1.01 % ) in the D ′ ′ layer. The observed fast axis polarization azimuths in the ray coordinate system indicate a TTI (transverse isotropy with a tilted axis of symmetry) style of anisotropy. Lattice Preferred Orientation (LPO) deformation of the palaeo‐subducted slabs experiencing high shear strain is a plausible explanation for the observed anisotropy beneath the IOGL. Key Points: Comprehensive study of splitting in high‐quality ScS waveforms corrected for UM anisotropy Clear evidence for anisotropy in the D″ layer beneath the Indian Ocean LPO deformation of palaeo‐subducted slabs experiencing high shear strain atop the CMB